2015
DOI: 10.1007/s10653-015-9767-z
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccessibility of selenium after human ingestion in relation to its chemical species and compartmentalization in maize

Abstract: Selenium is a micronutrient needed by all living organisms including humans, but often present in low concentration in food with possible deficiency. From another side, at higher concentrations in soils as observed in seleniferous regions of the world, and in function of its chemical species, Se can also induce (eco)toxicity. Root Se uptake was therefore studied in function of its initial form for maize (Zea mays L.), a plant widely cultivated for human and animal food over the world. Se phytotoxicity and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…They reported that the concentrations of these metals in cassava roots grown in petroleum-impacted soil were significantly higher than those in the corresponding control soil. They also observed that metal concentrations in the cassava strongly depended on the concentration in the soil and that the concentrations varied between the different parts of the plant as observed by Mombo et al (2016). Similarly, Kříbek et al (2014) also reported higher concentrations of various metals (Cu, Co, Zn, As, and Pb) in cassava leaves than in stems and roots.…”
Section: Plant Contamination By Metallic Trace Elements and Phytotoximentioning
confidence: 79%
See 4 more Smart Citations
“…They reported that the concentrations of these metals in cassava roots grown in petroleum-impacted soil were significantly higher than those in the corresponding control soil. They also observed that metal concentrations in the cassava strongly depended on the concentration in the soil and that the concentrations varied between the different parts of the plant as observed by Mombo et al (2016). Similarly, Kříbek et al (2014) also reported higher concentrations of various metals (Cu, Co, Zn, As, and Pb) in cassava leaves than in stems and roots.…”
Section: Plant Contamination By Metallic Trace Elements and Phytotoximentioning
confidence: 79%
“…TME trace metal element. By Mombo et al (2016) germination, root elongation, biomass, and inhibition of chlorophyll biosynthesis (Pourrut et al 2011;Austruy et al 2014). Heavy metal phytotoxicity in plants depends on numerous physiological and molecular functions of the metal and crop, such as the following: (i) uptake and binding to root exudates and cell wall constituents; (ii) chelation and complexation of metal ions by various substances such as phytochelatins, glutathiones, metallothioneins, amino acids, and organic acids; and (iii) activation of plant defense systems for proper functioning of metabolic pathways (Shahid et al 2013).…”
Section: Plant Contamination By Metallic Trace Elements and Phytotoximentioning
confidence: 99%
See 3 more Smart Citations